CONTENT ANALYSIS OF GRADUATE THESES WRITTEN IN THE FIELD OF ENVIRONMENTAL ACCOUNTING IN TURKEY - ZEYTİN, Mustafa (Atlas Journal, 2021)
The study aims to examine the master and doctoral theses on "environmental accounting" in YÖK (Turkish Council of Higher Education) National Thesis Centre in terms of content according to predetermined criteria. In line with this purpose, a total of 71 theses, 16 doctorate and 55 master, have been reached as of December 2020 through the website of YÖK National Thesis Centre. Since access permission was restricted by the authors of 8 of these theses, the content analysis of 63 theses was carried out. It is seen that the postgraduate studies with access permission are mostly made by Marmara University students; 43% of the theses are supervised by the professors, and the studies are based on empirical research. Besides, in the theses examined, it was seen that the qualitative (accounting) method was adopted more, production enterprises were selected as the sample group, and frequency analysis, correlation, regression, ANOVA and Factor analysis were used in the analysis of the data obtained. Based on these results, it can be suggested that researchers who will work in the field of "environmental accounting" should give more place to mixed analysis methods to address the issue in depth.